Humanized dental care for the transsexual community: literature review (Research, Society and Development, 2021)
Objective: To highlight and analyze how the humanized dental care of the transsexual population occurs and to identify the knowledge that the dental surgeon has about public policies for this population. Methodology: This is a study of narrative literature review. Literature review: It is important to emphasize the absence of transvestites and transsexuals in health services, especially in primary care, which should be the gateway to health services. As for the assistance to gays, lesbians, bisexuals, transvestites and transsexuals, violations of basic human rights by various social groups (including health professionals) such as segregation, prejudice, social marginalization, etc., promote the formulation of creating public policies specific health services for these audiences to ensure equity in care. Final Considerations: It is concluded that there must be a dignified service, making it necessary to invest in the preparation of professionals for specific treatments and care for the transsexual community.